Presence of infectious polyadenylated RNA in the coronavirus avian bronchitis virus - Schochetman, Gerald (Virology, 1977)
Avian infectious bronchitis virus (IBV) was radiolabeled for its nucleic acid component by growth in deembryonated chicken eggs. Purified virions of IBV have a buoyant density in linear sucrose gradients of 1.17-1.18 g/cm3 and contain approximately 4% RNA by weight. The genomic ribonucleic acid of IBV shows the following characteristic: (1) It consists of one size class of single-stranded RNA having a molecular weight of 5.5-5.7 x 108 and a sedimentation coefficient of about 48 S; (2) no evidence for subunit structure is apparent since the RNA resolves as a single species with the same electrophoretic mobility in polyacrylamide gels before and after heat denaturation; (3) at least 20–30% of the RNA molecules extracted from purified virions contain sequences of polyadenylic acid of approximately 4 S size; (4) RNA obtained from detergent-disrupted virus particles by phenol-chloroform extraction is infectious for cultures of chick embryo fibroblasts, giving rise to progeny virus which is lethal for embryonated eggs. These findings, together with the observation that IBV virions do not exhibit detectable transcriptase activity, support the conclusion that the genome of this coronavirus acts directly as a messenger RNA in eukaryotic cells.